Reflections about black education in Brazil: an approach for black women - Lima, Adaíles Aguiar; Custódio, Elivaldo Serrão (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
This study seeks to bring a brief reflection on the trajectory of black education in Brazil from colonial times to the present day, with a focus on black women. This is the preliminary result of an exploratory study of a qualitative nature. The results point to a trajectory of struggle for denied rights and a constant resistance to the adjustments of the dominant classes that solidified a society molded in the Eurocentric, hegemonic, racist thought, in which education, since the colonial period, was thought and directed to the Portuguese and, after that period, the dominant classes, always aiming at maintaining privileges, leaving the black population with domination and exploitation. In addition, the black woman was subjugated in a more painful way, as she suffered and still suffers prejudice and discrimination of color and gender.